Knowledge as a Factor Associated with Lifestyle in Controlling Hypertension - Iriana, Pramita; Yardes, Nelly; Sudrajat, Ace; Mahanani, Munifah Syamara; Malau, Paulus Hotmatua (JURNAL INFO KESEHATAN, 2022)
Hypertension is also understood as the "silent killer" as the symptoms of hypertension are frequently not experienced by the sufferer, hence, the majority of hypertension patients are unaware that they suffer from hypertension. Uncontrolled hypertension can harm multiple organs. Hypertension cannot be cured; however, it can be managed such that blood pressure stays within normal limits. Changes in lifestyle and pharmacological therapy are employed to control hypertension. The objective of this study is to investigate the association between hypertension patients' characteristics and amount of awareness about lifestyle in controlling hypertension. A descriptive analytic design with a cross sectional approach was administered in this investigation. This study included all hypertension patients who visited the Cibubur Village Health Center. Purposive sampling was utilized in this study, yielding 115 respondents. The analysis technique involved the Chi-Square test. Results: There was a relationship between age and lifestyle (p=0.044), the last education and lifestyle (p = 0.017), and the level of knowledge with lifestyle (p=0.000). Meanwhile, gender, occupation, and family history of hypertension did not possess a significant relationship with lifestyle in controlling hypertension. Future studies are suggested to examine the role of external environmental support in influencing lifestyle to control hypertension.